(untitled) (TẠP CHÍ KHOA HỌC TRƯỜNG ĐẠI HỌC TRÀ VINH, 2022)
Recently, permeable concrete has been considered one of the "Best Management Practices" in rainwater collection and cleaning. The outstanding properties of this type of concrete are its relatively high porosity (typically 15 ÷ 30% in volume) and the linking/connection of the internal pore system resulting in high water permeability and retention. However, one of the limitations to the widespread application of this eco-friendly material is the decrease of permeable capacity over time due to the clogging materials and the lack of regular maintenance. This paper performs an experimental approach for manufacturing permeable concrete that has both high water permeability and meets the strength requirement (1). At the same time, the influence of clogging sand and typical maintenance methods on the infiltration rate of permeable or pervious concrete is presented (2). Based on the literature review and obtained experimental results in this study, maintenance measures to ensure the required permeability for urban surface structures and sustainable surface water drainage are also proposed (3).